Driving Ability under Sertindole - Brunnauer, A.; Laux, G. (Pharmacopsychiatry, 2012)
Fitness to drive is an important prerequisite for the functional autonomy and thus also relevant for patients with a psychiatric illness. The efficacy of sertindole in the treatment of positive and negative schizophrenia symptoms has been shown in various studies. However, hitherto there exist no data about patients’ fitness to drive under sertindole.A non-randomized clinical study with 30 schizophrenic inpatients receiving sertindole (n=10), risperidone (n=10) or quetiapine (n=10) was conducted. Patients were tested under steady-state plasma level conditions prior to discharge to outpatient treatment. Data were collected with the computerized Act and React Testsystem (ART90) and the Wiener Determinationsgerät (WDG) measuring psychomotor skills relevant for fitness to drive.The main findings of this study are (i) that about 26% of schizophrenic patients, following psychopathologic stabilization and prior discharge to outpatient treatment show severe impairments with respect to driving skills. (ii) Statistically significant differences between atypical antipsychotics could neither be demonstrated on the level of the global driving ability score nor on individual functional domains essential for fitness to drive.With respect to driving skills no differences have been found between patients treated with sertindole, risperidone or quetiapine. However, a great proportion of schizophrenic patients partly remitted must be considered as unfit to drive, even when stabilized on treatment with atypical antipsychotics.
Keywords: driving ability; antipsychotic drugs; schizophrenia